Isolation and identification of types of biofilms- forming bacteria isolated from environmental samples and their production of beta- Lactamases enzymes (Texas Journal of Agriculture and Biological Sciences, 2022)
A biofilm is a community of microbes made up of microbial cells that attach to one another on living or nonliving surfaces within an extracellular polymeric material matrix that the microbes themselves have generated. The process of creating a biofilm involves several steps, beginning with attachment to a surface, followed by the development of a microcolony that results in the production of a three-dimensional structure, and eventually maturation and separation. Numerous bacterial species can communicate with one another during biofilm formation thanks to a special process called quorum sensing. The QS system enables communication between intraspecies and interspecies, which involves, in terms of biofilm formation, food shortages, and environmental stress conditions, such as disinfectants, antibiotics, bacterial colonisation, the identification of irksome species, the establishment of normal intestinal flora, well as the prevention of harmful intestinal flora. The biofilm's matrix may allow for the diffusion of antibiotics. Exopolysaccharide acts as a physical barrier, which affects the diffusion or penetration of antibiotics into deeper levels of biofilm. The flow of molecules into the centre of the biofilm is slowed down when they come into direct contact with this matrix, leading to antibiotic resistance. The presence of neutralising enzymes that break down or inactivate antibiotics may be the cause of antibiotic resistance in biofilm. These enzymes are proteins that increase resistance through biochemical processes like hydrolysis and modification of antimicrobials